Implementasi Nilai-Nilai Pendidikan Ibadah dalam Surah Al-Muzammil Ayat 20 Di Madrasah Ibtidaiyah Swasta Al-Ba’ani Kota Bengkulu - Nurhaiyah Sormin; Ahmad Suradi; Mindani Mindani (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
This study uses a qualitative design with the type of field research. Data were collected by using observation, interviews, and documentation. The results of the study indicate that the implementation of religious education values in Surah Al-Muzammil verse 20 at MI Al-Ba’ani Bengkulu City is in the form of religious programs such as; pray, read the Qur’an, teach children to give alms and zakat. The prayer program was carried out at the madrasa is the Duhah prayer and the Dzhur prayer. The activity of reading the Qur’an juz 30 which was carried out before starting the lesson. Madrasah Ibtidaiyah Al-Ba’ani also implements the alms program every Friday, but the program has not yet been fully implemented, due to the economic background of the students parents who have not made it possible to run the alms program on Friday. And Madrasah Ibtidaiyah Al-Ba’ani also implements a zakat program, where zakat payment activities ware carried out at the Madrasah Ibtidaiyah, then zakat distribution were given to students, orphans, the rich and the poor.